Liberated love : release codependent patterns and create the love you desire - Groves, Mark, 1979-; McBeath, Kylie (St. Martin's Essentials, 2024)
"We all desire great love. Yet, there seems to be a lot in the way when it comes to cultivating a relationship we crave. Why is that? It's time for a new template - one rooted in choice, truth, safety, and respect. To get us there, Mark Groves and Kylie McBeath, champions of positive philosophy, provide us a roadmap, one they walked themselves, to step out of protection mode and into connection mode. Groves and McBeath's work-through their Create the Love seminars, workbooks, and consultation programs-have educated a new generation of relationship seekers on the best ways to practice and cultivate love. In Liberated Love, you'll explore your original relationship blueprint and learn how it informs your current relationships (spoiler alert: it's often a pretty direct line), and discover how limitation can be the key to finding freedom and experiencing full, fully-realized love with another person. Equipped with real-life situations and stories, exercises, rituals, and tools that lead to productive self-examination, Groves and McBeath illuminate how to be aware of our most instinctual defenses, survival strategies, and coping mechanisms, how to have conversations about relationships without turning them into "relationship conversations," and how to date in a way that protects your heart as you open it up to new possibilities. In these pages, in a format you'll want to turn to again and again, you'll learn how to begin and maintain relationships that allow true self-expression-to feel safe and to feel real, involving, sustaining love"--